The role of copper dysregulation in Wilson disease: an expert opinion - Stremmel, Wolfgang; Weiskirchen, Ralf (Frontiers in Medicine, 2025)
The handling of free copper is a crucial aspect of copper metabolism. Any dysfunction in this process can lead to the pathophysiology of diseases, such as Wilson disease. This disorder, characterized by an excess of copper in the liver, occurs when the body is unable to excrete copper into bile. The symptoms of the disease result from the accumulation of free copper in liver cells, leading to hepatocellular injury and the release of copper into the bloodstream. This, in turn, causes damage in other areas of the body, such as the brain. The primary goal of therapy is to convert toxic free copper into harmless complexes, rather than simply removing copper from the body.